“Persepsi Siswa Kelas X Madrasah Aliyah Terpadu Al Munawaroh Ngemplak Jombang terhadap Kesulitan dan Kemudahan Penguasaan 4 Maharah” (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2025)
This study aims to explore the perceptions of 10th grade students of Al Munawaroh Ngemplak Jombang Integrated Islamic Senior High School regarding the difficulties and ease in mastering Arabic language skills, with a focus on reading (qira’ah) and listening (istima’) skills. Through a case study approach, data were collected using a questionnaire given to students to identify the challenges and ease they face in learning these skills. This study also analyzes the factors that influence the success or difficulty in mastering Arabic language skills, both from internal (motivation, learning habits) and external (teaching materials, teaching) aspects. The results showed that most students found it difficult to understand complex Arabic texts and understand fast conversations in Arabic. However, they also noted the ease in mastering basic vocabulary and understanding simple sentence structures. This study provides important insights into the challenges faced by students in learning Arabic and offers recommendations for the development of more effective teaching methods, especially in improving students' listening and reading skills. Thus, these findings are expected to contribute to the development of the curriculum and practice of teaching Arabic at the Islamic Senior High School level.